Multitargeted Herbal Prescription So Shiho Tang: A Scoping Review on Biomarkers for the Evaluation of Therapeutic Effects - Nguyen Khoi Song Tran; Ji Hwan Lee; Myong Jin Lee; Jun Yeon Park; Ki Sung Kang (MDPI AG, 2023)
Alternative medicines, especially herbal remedies, have been employed to treat infections and metabolism-related chronic inflammation because their safety and multidimensional therapeutic potential outweigh those of synthetic drugs. So Shiho Tang (SSHT), a well-known Oriental prescription (Xiao Chai Hu Tang in Chinese) composed of seven herbs, is traditionally prescribed to treat various viral infections and chronic metabolic disorders in Asia with or without the support of other natural medicines. To provide a general background on how SSHT is used as a medicinal alternative, we conducted a scoping review using the PubMed database system. Among the 453 articles, 76 studies used aqueous extracts of SSHT alone. This result included seven clinical studies and 69 basic studies: cell-based, animal-based, and ex vivo studies. The in vitro and clinical reports mainly focus on hepatic infection and hepatocarcinoma, and the documentation of in vivo tests of SSHT presents a wide range of effects on cancer, fibrosis, inflammation, and several metabolic disorder symptoms. Additionally, among the seven clinical records, two reverse-effect case studies were reported in middle-aged patients. In brief, this systematic review provides general knowledge on the natural remedy SSHT and its potential in phytotherapeutic primary health care.